Adoption rate of land clearing techniques and their effects on some soil fertility parameters of an Alfisol in southwestern Nigeria - M. B. Adewole; U. C. Anyahara (African Journal of Environmental Economics and Management, 2020)
This study aims at investigating the determining factors of land clearing techniques and their effects on some soil fertility parameters of an alfisol in a derived savanna agroecology of southwestern Nigeria. The stratified simple random technique was used to obtain primary data using structured questionnaire and also to collect topsoil from 33% of the respondents’ farms for the soil physicochemical properties in 2008 and 2009. Data collected were analyzed using appropriate statistical tools. Determining factors identified for the choice of land clearing techniques include: sex, family size, level of education, land size, level of awareness and farmers’ source of income. The study identified manual stumping as the land clearing technique adopted by most farmers, but with least adverse effect on soil fertility parameters measured. Bulldozing was the least adopted method, but with negative impact on soil properties. Lack of fund, low level of education and poor government intervention were identified factors keeping agriculture at its subsistence level in the study area. Hence, sound enlightenment campaign program through radio jingle, posters and handbills in local languages on appropriate land clearing technique(s) most adequate for a typical humid tropics soil is desirable for sustainable and sound soil health.